If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -4 + 2(x + 1) = 10 Reorder the terms: x + -4 + 2(1 + x) = 10 x + -4 + (1 * 2 + x * 2) = 10 x + -4 + (2 + 2x) = 10 Reorder the terms: -4 + 2 + x + 2x = 10 Combine like terms: -4 + 2 = -2 -2 + x + 2x = 10 Combine like terms: x + 2x = 3x -2 + 3x = 10 Solving -2 + 3x = 10 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 3x = 10 + 2 Combine like terms: -2 + 2 = 0 0 + 3x = 10 + 2 3x = 10 + 2 Combine like terms: 10 + 2 = 12 3x = 12 Divide each side by '3'. x = 4 Simplifying x = 4
| 1+2+-3+-4+5= | | 3x-4=2+7 | | 20x+11=25-14 | | 139-5x=3x+16 | | 12(3x+5)-6(2x-3)=4x-22 | | (x+5)(2x-1)= | | 5/2+5w-6=-3 | | 3+-17=-15 | | 7b-3=6b+7 | | 6x+3y=-33 | | -5+-2-3= | | z-3=-1 | | 20x^2-15x+16x-12=0 | | 2q+5=17 | | -5+-2+-3= | | 2+-14=-25 | | 13m+-17=399 | | 20x+5=1.4 | | -6x-30=6x-30 | | 80+90+x=180 | | =x(x+2) | | 1050+700+5x=800+300+7x | | x^2+2*x-5= | | 6x-5=14x-35 | | 3x^6-8x^3-28=0 | | -2+-4+-12= | | -3x--4=19 | | =5(2x-6) | | 5a-6=2a+15 | | 38-4=5 | | 2(10+x)=6x | | =9(x+7) |